Biomimetic Hydrogels for In Vitro Modelling of Nucleus Pulposus Degeneration: Effects of Extracellular Matrix Compositional Change on Physicochemical Properties and Cell Phenotype - Narjes Rashidi; Nicholas Dowell; Derek Covill; John Shepperd; Matteo Santin (Journal of Functional Biomaterials, 2025)
The intervertebral disc, an anatomical compartment interposed between vertebral bodies, plays a key role in spine flexibility and compression loading. It comprises three tissues: the nucleus pulposus, the annulus fibrosus, and the end plates. Degeneration-related changes in the extracellular matrix of the nucleus pulposus upon ageing or pathological conditions prompted the present investigation into the impact of proteoglycan reduction, the main constituent of the healthy nucleus pulposus, on its physicochemical properties and cellular phenotypical changes. To mimic the native extracellular matrix, three-dimensional NP-mimicking constructs were developed using a biomimetic hydrogel composed of collagen type I, collagen type II, and proteoglycans. This system was fabricated using a bottom-up approach, employing highly pure monomeric collagen types I and II, which were induced to form a reconstituted fibrillar structure closely resembling the natural NP microenvironment. A comprehensive physicochemical characterization was conducted at varying proteoglycan percentages using scanning electron microscopy (SEM), FTIR, rheological tests, and water retention property analysis. The effect of microenvironment changes on the phenotype of nucleus pulposus cells was studied by their encapsulation within the various collagen–proteoglycan hydrogels. The morphological and immunochemistry analysis of the cells was performed to study the cell–matrix adhesion pathways and the expression of the cellular regulator hypoxia-inducible factor 1 alpha. These were linked to the analysis of the synthesis of healthy or pathological extracellular matrix components. The findings reveal that the reduction in proteoglycan content in the nucleus pulposus tissue triggers a pathological pathway, impairing the rheological and water retention properties. Consequently, the cell phenotypes are altered, inducing the synthesis of collagen type I rather than securing the natural physiological remodelling process by the synthesis of collagen type II and proteoglycans. Identifying the proteoglycan content threshold that triggers these pathological phenotypical changes could provide new diagnostic markers and early therapeutic strategies for intervertebral disc degeneration.